A Small-Molecule Probe for Selective Profiling and Imaging of Monoamine OxidaseB Activities in Models of Parkinson's Disease - Li, Lin; Zhang, Cheng-Wu; Ge, Jingyan; Qian, Linghui; Chai, Bing-Han; Zhu, Qing; Lee, Jun-Seok; Lim, Kah-Leong; Yao, Shao Q. (John Wiley & Sons Ltd., 2015)
The design of the first dual-purpose activity-based probe of monoamine oxidaseB (MAO-B) is reported. This probe is highly selective towards MAO-B, even at high MAO-A expression levels, and could sensitively report endogenous MAO-B activities by both insitu proteome profiling and live-cell bioimaging. With a built-in imaging module as part of the probe design, the probe was able to accomplish what all previously reported MAO-B imaging probes failed to do thus far: the live-cell imaging of MAO-B activities without encountering diffusion problems.
Keywords: MAO-A; TARGET IDENTIFICATION; FLUOROGENIC PROBES; B INHIBITORS; APOPTOSIS; EXPRESSION